2005
DOI: 10.1021/bm049427e
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Density Effect on Biorecognition by PEGylated Gold Nanoparticles:  Regulated Interaction of RCA120 Lectin with Lactose Installed to the Distal End of Tethered PEG Strands on Gold Surface

Abstract: PEGylated gold nanoparticles (diameter: 20 nm) possessing various functionalities of lactose ligand on the distal end of tethered PEG ranging from 0 to 65% were prepared to explore the effect of ligand density of the nanoparticles on their lectin binding property. UV-visible spectra of the aqueous solution of the nanoparticles revealed that the strong steric stabilization property of the PEG layer lends the nanoparticles high dispersion stability even under the physiological salt concentration (ionic strength,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(107 citation statements)
references
References 24 publications
5
102
0
Order By: Relevance
“…5c, it can also be seen that the introduction of BSA improves the stability of the AuNPs functionalized with 3.4 μg/ml of PEG. It has been previously reported that BSA binds to AuNPs [30,42]. The observation here that BSA does not affect the stability of AuNPs with denser PEG coatings may be a result of the influence of any BSA attachment being masked by the effect of the higher levels of PEG and the denser coating impeding protein attachment.…”
Section: Colloid Stability Testsmentioning
confidence: 43%
“…5c, it can also be seen that the introduction of BSA improves the stability of the AuNPs functionalized with 3.4 μg/ml of PEG. It has been previously reported that BSA binds to AuNPs [30,42]. The observation here that BSA does not affect the stability of AuNPs with denser PEG coatings may be a result of the influence of any BSA attachment being masked by the effect of the higher levels of PEG and the denser coating impeding protein attachment.…”
Section: Colloid Stability Testsmentioning
confidence: 43%
“…70,85 These authors synthesised gold nanoparticles stabilised with a mixed monolayer containing lactose-PEG-SH and acetal-PEG-SH ligands. The surface coverage of the glyconanoparticles with lactose was 0%, 20%, 40% and 65%.…”
Section: Carbohydrate Density On the Nanoparticle Surfacementioning
confidence: 99%
“…AuNPs were coated with thio-polyethylene glycol-COOH (thio-PEG-COOH) (3000 MW, Rapp Polymere, Tü bingen, Germany) [14]. These were linked to Herceptin (Genentech, South San Francisco, CA) or mouse immunoglobulin G (IgG, Sigma, St Louis, MO) using 1-ethyl-3-(39-(dimethylamino)propyl)-carbodiimide (EDC) and N-hydroxysuccinimide (Sigma) [15].…”
Section: Gold Nanoparticlesmentioning
confidence: 99%